Effects of Vitamin C in Indian Gooseberry (𝙋𝙝𝙮𝙡𝙡𝙖𝙣𝙩𝙝𝙪𝙨 𝙚𝙢𝙗𝙡𝙞𝙘𝙖) Extract on Growth Performance, Blood Biochemical, Non-Specific Immune Responses and Bacterial Resistance, 𝙎𝙩𝙧𝙚𝙥𝙩𝙤𝙘𝙤𝙘𝙘𝙪𝙨 𝙖𝙜𝙖𝙡𝙖𝙘𝙩𝙞𝙖𝙚 in Nile tilapia (𝙊𝙧𝙚𝙤𝙘𝙝𝙧𝙤𝙢𝙞𝙨 𝙣𝙞𝙡𝙤𝙩𝙞𝙘𝙪𝙨) - Kannika, Korntip; Panprommin, Dutrudi; Soontomprasit, Kanyanat; Hensuk, Pattanapong; Sadudee , Sahutsa; Piangtaisong , Kanyanee (Burapha Science Journal, 2024)
Background and Objectives : The aim of this research is to determine the effects of vitamin C in Indian gooseberry (Phyllanthus emblica) extract on growth performance, blood biochemical, non-specific immune response and bacterial resistance against, Streptococcus agalactiae in Nile tilapia (Oreochromis niloticus) Methodology : A completely randomized design (CRD) was used in this experiment, Five groups of Nile tilapia were fed experimental diets containing control group (without vitamin C), T1-T3: supplemented with vitamin C (natural ascorbic acid) from Indian gooseberry extract at 3, 6, and 10%, and T4: supplemented synthetic vitamin C at 3 g/kg for 60 days. Main Results : The experimental fish supplemented with Indian gooseberry extract at 3 % had a final average weight, weight gain, average dairy gain (ADG) and the feed conversion ratio (FCR) were not significantly different compared with Indian gooseberry extract at 10 % and synthetic vitamin C groups (P > 0.05). Nile tilapia in the experimental group were fed with vitamin C (natural ascorbic acid) from Indian gooseberry extract and synthetic vitamin C has a growth rate, non specific immune response; Phagocytic activity and lysozyme activity; and bacterial resistance, S. agalactiae significantly better than control group (P<0.05). Conclusions : The results of this study can be seen that Indian gooseberry (P. emblica) extract can be used as a supplemented in tilapia diets to replace the use of synthetic vitamin C.